DETERMINATION OF PHYSICAL PARAMETERS OF DEPOSITS ON BOILER HEATING SURFACES USING METHODS OF MATHEMATICAL MODELING UNDER CONDITIONS OF LIMITED INFORMATION - N. B. Karnitsky; T. V. Kadach (Наука и техника)
The paper considers methods of a numerical experiment that make it possible to complement and develop experimental results concerning characteristics of external deposits on boiler heatng surfaces while using limited information.